Banalność zła na jerozolimskiej scenie. Proces Adolfa Eichmanna jako spektakl - Budzik, Jagoda (Studia Azjatystyczne, 2016)
The article is a reflection on the topic of connection between a legal procedure and a performance and its role during the trial of Adolf Eichmann. After almost two decades of intentional silence surrounding the subject of the Holocaust survivors in the official Israeli discourse, during the trial of Adolf Eichmann, which took place in Jerusalem in 1961, for the first time the victims where given an opportunity to speak about their experiences to the public, wheras the Israeli society of early sixties, for the first time faced these stories. In the paper the author argues that the trial of Adolf Eichmann was not only a legal procedure, but also – in the light of strategies determining its final shape – a performance that was supposed to construct a new perspecitve of Holocaust narratives in Israel of early sixties.